Perspectives From Canadian People With Visual Impairments in Everyday Environments Outside the Home: Qualitative Insights for Assistive Technology Development - Prajjol Raj Puri; Andréanne Coutaller; Frédérique Gwade; Soutongnoma Safiata Kabore; Deborah Annan; Joseph Paul Nemargut (JMIR Rehabilitation and Assistive Technologies)
Abstract BackgroundDespite the abundance of assistive devices available, the accomplishment of many everyday tasks remains complex for people with visual impairments. While several studies have been conducted to identify the obstacles encountered when moving around outdoors, current knowledge is less abundant when it comes to the difficulties encountered in complex, indoor environments. ObjectiveThis study aimed to identify the most important obstacles and facilitators encountered in everyday indoor travel environments outside the home for people with low vision and blindness. MethodsData were collected from 20 participants with varying levels of vision from several cities across Canada in 2 web-based focus groups in both English and French. Using open-ended questions, participants shared obstacles and facilitators experienced or imagined during independent navigation in the following scenarios: coffee shop, hospital, big-box store, party with friends, and bus rides. Thematic analysis was conducted, and responses were either categorized as barriers or facilitators for each scenario. These were ranked by all participants via email according to their perceived importance in completing each scenario. ResultsAcross scenarios, the principal barriers to perceived success were inaccessible signage, difficulties walking around, problems finding a specific location, and unsuccessful interactions with others. The main facilitators across scenarios were helpful interactions with others, planning, accessible signage, and websites. The use of mobile apps was discussed but ranked as less important by participants. Though similar among the French and English groups, the rankings of the different facilitators and barriers were largely scenario-specific. The most barriers were mentioned in the coffee shop (n=8), followed by the department store (n=7) and bus or metro (n=7) for the English group, whereas the most barriers were in the department store (n=9), followed by the hospital or clinic (n=7) and coffee shop (n=6) for the French group. ConclusionsThough promising technologies have been developed to resolve some of the issues surrounding indoor navigation for people with visual impairments, they were not perceived as helpful as some other traditional methods of assistance, such as asking for help, by our participants. For the successful incorporation of indoor navigation technologies, it is important to understand how they integrate into the experience of people as they move in these dynamic environments. The successful use of technology is only possible if the physical environment permits and facilitates independent navigation.